2018
DOI: 10.1093/infdis/jiy713
|View full text |Cite
|
Sign up to set email alerts
|

In vivo role of capsular polysaccharide in Mycoplasma mycoides

Abstract: Many Mycoplasma species have been shown to possess capsular polysaccharides (CPSs). We challenged goats with a CPS-defective or its CPS-possessing parental Mycoplasma mycoides strain. The CPS-defective strain was attenuated, demonstrating that the CPS consisting of galactofuranose is a virulence trait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…The second aim was to verify this attenuation in vivo using the native host, since no rodent animal models for highly virulent M. mycoides exist (Jores et al, 2013). Many candidate virulence factors of M. mycoides have been suggested but, none except the capsular polysaccharide (Jores et al, 2018) have ever been confirmed according to Falkow’s postulates in vivo (Falkow, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The second aim was to verify this attenuation in vivo using the native host, since no rodent animal models for highly virulent M. mycoides exist (Jores et al, 2013). Many candidate virulence factors of M. mycoides have been suggested but, none except the capsular polysaccharide (Jores et al, 2018) have ever been confirmed according to Falkow’s postulates in vivo (Falkow, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In the control group, 5 goats out of 8 met the endpoint criteria before the envisaged end of the trial (i.e., 35 dpi) and were euthanized in the course of the experiment, whereas only 1 goat (animal CM135) out of 8 met the same criteria in the obg group (Fig. 4A) (24). M.…”
Section: Resultsmentioning
confidence: 99%
“…The second aim was to verify this attenuation in vivo using the native host, since no rodent animal models for highly virulent M. mycoides exist (3). Many candidate virulence factors of Mycoplasma mycoides have been suggested but, all except capsular polysaccharide (19) have never been confirmed according to Falkow’s postulates in vivo (20).…”
Section: Discussionmentioning
confidence: 99%